Prevalence and correlates of dyslipidemia in first-episode and drug-naïve major depressive disorder patients with comorbid abnormal glucose metabolism: Sex differences - Zhu, Quanfeng; Zheng, Yali; Lang, XiaoE; Fu, Zhengchuang; Zhang, Peng; Jiang, Guojun; Zhang, Xiangyang (Frontiers in Psychiatry, 2023)
Background: Lipid metabolism is associated with glucose metabolism, but whether there are variations between sexes in risk factors and prevalence of abnormal lipid metabolism in major depressive disorder (MDD) patients with glucose metabolism abnormalities remains ambiguous. In the present study, the frequency and risk factors of dyslipidemia in first-episode and drug-naïve (FEDN) MDD patients with dysglycemia were examined according to sex. Methods: 1718 FEDN MDD patients were recruited and their demographic data, clinical data, various biochemical indicators and scale assessment scores including 17-item Hamilton Rating Scale for Depression (HAMD-17), 14-item Hamilton Anxiety Rating Scale (HAMA-14) and positive subscale of the Positive and Negative Syndrome Scale (PANSS) were collected. Results: The prevalence of abnormal lipid metabolism in both male and female MDD patients with abnormal glucose metabolism was higher than that in patients without abnormal glucose metabolism. Among male MDD patients with abnormal glucose metabolism, TC was positively correlated with HAMD score, TSH and TgAb levels, but negatively correlated with PANSS positive subscale scores. LDL-C was positively correlated with TSH and BMI, but negatively correlated with PANSS positive subscale scores. HDL-C was negatively correlated with TSH levels. Among females, TC was positively correlated with HAMD score, TSH and BMI, but negatively correlated with PANSS positive subscale score. LDL-C was positively correlated with HADM score and negatively correlated with FT3 level. HDL-C was negatively correlated with TSH and BMI levels. Conclusions: There are sex differences in the correlated factors of lipid markers in MDD patients with impaired glucose.